The current status of cell‐free human papillomavirus DNA as a biomarker in cervical cancer and other HPV‐associated tumors: A review. Issue 11 (27th October 2022) - Sivars, Lars; Palsdottir, Kolbrun; Crona Guterstam, Ylva; Falconer, Henrik; Hellman, Kristina; Tham, Emma
Abstract: Tumor cells release fragments of their DNA into the circulation, so called cell‐free tumor DNA (ctDNA), allowing for analysis of tumor DNA in a simple blood test, that is, liquid biopsy. Cervical cancer is one of the most common malignancies among women worldwide and high‐risk human papillomavirus (HR‐HPV) is the cause of the majority of cases. HR‐HPV integrates into the host genome and is often present in multiple copies per cell and should thus also be released as ctDNA. Such ctHPV DNA is therefore a possible biomarker in cervical cancer. In this review, we first give a background on ctDNA in general and then a comprehensive review of studies on ctHPV DNA in cervical cancer and pre‐malignant lesions that may develop in cervical cancer. Furthermore, studies on ctHPV DNA in other HPV related malignancies (eg,  head‐and‐neck and anogenital cancers) are briefly reviewed. We conclude that detection of ctHPV DNA in plasma from patients with cervical cancer is feasible, although optimized protocols and ultra‐sensitive techniques are required for sufficient sensitivity. Results from retrospective studies in both cervical cancer and other HPV‐related malignancies suggests that ctHPV DNA is a promising prognostic biomarker, for example, for detecting relapses early. This paves the way for larger, preferably prospective studies investigating the clinical value of ctHPV DNA as a biomarker in cervical cancer. However, there are conflicting results whether ctHPV DNA can be found in blood from patients with pre‐malignant lesions and further studies are needed to fully elucidate this question. Abstract :